Investigation of the relationship between ionised and total calcium in dogs with ionised hypercalcaemia. (11th February 2020) - Tørnqvist‐Johnsen, C.; Schnabel, T.; Gow, A. G.; Del‐Pozo, J.; Milne, E.; Macklin, V.; Fisher, C.; Handel, I.; Mellanby, R. J.
Abstract : Objectives: To investigate the relationship between total and ionised calcium concentrations in dogs with ionised hypercalcaemia and to evaluate how albumin influences this relationship. Methods: Initially, a reference interval for ionised and total calcium was established using a large population of healthy adult dogs. Our teaching hospital clinical database was searched to identify adult dogs with ionised hypercalcaemia between 2012 and 2017, a time frame when the same sample handling and analysis protocols were in place as for the healthy reference interval population. The relationship between ionised and total calcium concentrations was then examined in the ionised hypercalcaemia population. Results: Based on biochemical analysis of 351 healthy adult dogs, a reference interval of 1.18 to 1.53 mmol/L for ionised calcium and 2.24 to 2.85 mmol/L for total calcium was established. Using these reference intervals, 63 dogs with ionised hypercalcaemia were identified, of which 23 did not have total hypercalcaemia. Only seven of the 23 dogs with ionised hypercalcaemia and total calcium below the upper limit of the reference interval had hypoalbuminemia. The majority of dogs with ionised hypercalcemia and normal total calcium had a modest increase in ionised calcium. Clinical Significance: If relying on total calcium alone, more than one third of dogs with ionised hypercalcaemia will be classified as normocalcaemic and the majority of these dogs had normal serum albumin.